Pelatihan Pembuatan Peta Resiko Bencana Berbasis ArcGIS di Desa Kopang Rembiga Lombok Tengah - Muslimin Muslimin; Rifaid Rifaid; Rudi Arrahman; Muhromi Haspiadi; Maulana Ilmiyardhi; Muhammad Firman Hidayatullah; Andri Pratando (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Kopang Rembiga Village has a high vulnerability to natural disasters, such as floods, earthquakes and tornadoes. Finally, on March 13, 2024, a tornado hit Kopang Village and caused around 27 houses to be severely damaged (Antara, 2024). The Tornado Disaster in Central Lombok, especially in Rembiga Village, did not occur only this time, but in 2019 it also destroyed dozens of houses in Kopang Rembiga village, the incident occurred on Thursday, December 19, 2019. This service activity was carried out with the aim of conducting training on Making ArcGIS-Based Disaster Risk Maps in Kopang Rembiga Village, Central Lombok. The results of the ArcGIS-Based Disaster Risk Map Making training, in making disaster risk maps, it can be concluded that this activity has an impact, namely the existence of a disaster risk map in Kopang Rembige Village, Central Lombok, which is very informative so that it makes it easier for the community to use disaster risk maps independently to.